Indigenous Rights - Kingi, Pauline (The Treaty is always speaking: Te reo o te tiriti mai rano, 1989)
Keywords: civil Rights; history; human rights; indigenous rights; social life and customs; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Chapter Seventeen: 'As for these blankets, burn them' Māori and Indigeneity - Hokowhitu, Brendan (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"–Publisher's information.
Keywords: government relations; history; identity; indigenous rights; pan-indigenous movement; social conditions; tikanga | indigenous law; tāngata whenua